N-Butylidenephthalide exhibits protection against neurotoxicity through regulation of tryptophan 2, 3 dioxygenase in spinocerebellar ataxia type 3. (1st May 2017) - Rajamani, Karthyayani; Liu, Jen-Wei; Wu, Cheng-Han; Chiang, I-Tsang; You, Deng-Huwei; Lin, Si-Yin; Hsieh, Dean-Kuo; Lin, Shinn-Zong; Harn, Horng-Jyh; Chiou, Tzyy-Wen
Abstract: Spinocerebellar ataxia type 3 or Machado-Joseph disease (SCA3/MJD) is characterized by the repetition of a CAG codon in the ataxin-3 gene ( ATXN3 ), which leads to the formation of an elongated mutant ATXN3 protein that can neither be denatured nor undergo proteolysis in the normal manner. This abnormal proteolysis leads to the accumulation of cleaved fragments, which have been identified as toxic and further they act as a seed for more aggregate formation, thereby increasing toxicity in neuronal cells. To date, there have been few studies or treatment strategies that have focused on controlling toxic fragment formation. The aim of this study is to develop a potential treatment strategy for addressing the complications of toxic fragment formation and to provide an alternative treatment strategy for SCA3. Our preliminary data on anti-aggregation and toxic fragment formation using an HEK (human embryonic kidney cells) 293T-84Q-eGFP (green fluorescent protein) cell model identified n -butylidenephthalide ( n -BP) as a potential drug treatment for SCA3. n -BP decreased toxic fragment formation in both SCA3 cell and animal models. Moreover, results showed that n -BP can improve gait, motor coordination, and activity in SCA3 mice. To comprehend the molecular basis behind the control of toxic fragment formation, we used microarray analysis to identify tryptophan metabolism as a major player in controlling the fate of mutant ATXN3 aggregates. We also demonstrated that n- BP functions by regulating the early part of the kynurenine pathway through the downregulation of tryptophan 2, 3-dioxygenase (TDO2), which decreases the downstream neurotoxic product, quinolinic acid (QA). In addition, through the control of TDO2, n -BP also decreases active calpain levels, an important enzyme involved in the proteolysis of mutant ATXN3, thereby decreasing toxic fragment formation and associated neurotoxicity. Collectively, these findings indicate a correlation between n -BP, TDO2, QA, calpain, and toxic fragment formation. Thus, this study contributes to a better understanding of the molecular interactions involved in SCA3, and provides a novel potential treatment strategy for this neurodegenerative disease. Graphical abstract: Highlights: n -BP has anti-aggregating and pro-proliferative effect which aid in improvement of the pathological state of SCA3 mice. In SCA3, TDO2 has been observed to be upregulated which in turn upregulates downstream product QA. QA being an agonist of NMDA-R further may increase the influx of Ca 2+ ions which increases Ca 2+ dependent calpain activity. Calpain through proteolysis cleaves mutant ATXN3 to form toxic fragment. Hence, n -BP may decrease toxic fragment formation through its activity on TDO2 and improve the SCA3 neuropathology.